In the dramatists’ own words, why make use of myth: Unamuno, Pemán, Buero Vallejo - Silva Sánchez, Tomás (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper investigates the association between the plays Fedraby Miguel de Unamuno, Antígonaby José María Pemán and La tejedora de sueñosby Antonio Buero Vallejo. Although their authors represent different conceptions and stages of the 20th century Spanish theatre, the three of them coincided in a self-confessed interest in the ancient Greek tragedy and in their desire to perform new versions of the myths. Contrasting the particular interest and objectives of Unamuno, Pemán and Buero will shed some light on both the differences and the possible common elements between their dramatic recreations and will provide an overview of the treatment of the myth in the 20th century Spanish theatre.